Bălgarija - Makedonija - Slovenija: mežkulturni dialozi v XXI vek : recenzirana kolektivna naučna monografija = Bugarija - Makedonija - Slovenija : meǵukulturni dijalozi vo XXI vek = Bolgarija - Makedonija - Slovenija : medkulturni dialogi v XXI stoletju - Subiotto, Namita; Dimitrov, Ljudmil (Nacionalno izdatelstvo za obrazovanie i nauka "Az-buki", 2019)
The collective monograph comprises papers from the International Conference “Bulgaria – Macedonia – Slovenia: Intercultural Dialogue in the 21st c.” (Ljubljana, May 23 – 25, 2019). It is the first ever scientific conference aimed not only to highlight the specific problems of the three South Slavic countries, but also to look for perspective concepts for our closer spiritual rapprochement. (DE-1a)